2018
DOI: 10.1002/2017jg004084
|View full text |Cite
|
Sign up to set email alerts
|

Model‐Data Fusion to Test Hypothesized Drivers of Lake Carbon Cycling Reveals Importance of Physical Controls

Abstract: Formal integration of models and data to test hypotheses about the processes controlling carbon dynamics in lakes is rare, despite the importance of lakes in the carbon cycle. We built a suite of models (n = 102) representing different hypotheses about lake carbon processing, fit these models to data from a north‐temperate lake using data assimilation, and identified which processes were essential for adequately describing the observations. The hypotheses that we tested concerned organic matter lability and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Long-term monitoring of whole ecosystems can help identify variations related to their environmental drivers, because they are likely to include significant variations of these drivers without the scaling problem of experimental assessments. Among these drivers, physical features are the least studied in relation to their effects on metabolism, in part due to the complexity of disentangling the simultaneous effects of multiple drivers ( Hoellein, Bruesewitz & Richardson, 2013 ; Coloso, Cole & Pace, 2011 ; Hararuk et al, 2018 ). Nutrients are among the main drivers of primary production in oligotrophic and mesotrophic conditions, hindering the identification of the effects of physical features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term monitoring of whole ecosystems can help identify variations related to their environmental drivers, because they are likely to include significant variations of these drivers without the scaling problem of experimental assessments. Among these drivers, physical features are the least studied in relation to their effects on metabolism, in part due to the complexity of disentangling the simultaneous effects of multiple drivers ( Hoellein, Bruesewitz & Richardson, 2013 ; Coloso, Cole & Pace, 2011 ; Hararuk et al, 2018 ). Nutrients are among the main drivers of primary production in oligotrophic and mesotrophic conditions, hindering the identification of the effects of physical features.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrients are among the main drivers of primary production in oligotrophic and mesotrophic conditions, hindering the identification of the effects of physical features. Because of this, in eutrophic and hypertrophic systems, where nutrient availability is not limiting, the effects of physical drivers may be easier to isolate and quantify (e.g., Coloso, Cole & Pace, 2011 ; Hararuk et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, sometimes it is difficult to distinguish which processes are important for accurately predicting system dynamics due to equifinality in estimated parameters or insensitive model structures. For example, Hararuk et al () found it difficult to distinguish between biodegradation and photodegradation rates as these rates were additive and drivers for each process were positively correlated. In such cases, assimilating additional sources of information to constrain processes or structure can help; for example, in situ incubation experiments could be conducted to help constrain rates of photodegradation and biodegradation.…”
Section: Resultsmentioning
confidence: 99%
“…Although we include many essential processes for describing lake C dynamics when assimilating real observations, we did not explicitly test different model structures (other than including carbonate equilibria dynamics, see Supporting Information), which is another utility of data assimilation. For an example of a robust model structure comparison (102 different models) using data assimilation with the same lake dataset used in this analysis, see Hararuk et al (). While our model structure performed well when assimilating real observations from East Long Lake, it is unclear if the same model structures used here and in Hararuk et al () will perform equally well across different lakes.…”
Section: Comments and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation